The role of sleep dysfunction in temporomandibular onset and progression: A systematic review and meta‐analyses. (14th December 2020) - Burr, Meghan R.; Naze, Garrett S.; Shaffer, Stephen M.; Emerson, Alicia J.
Abstract: Background: Painful temporomandibular (TM) disorders result in 4.3 billion dollars spent annually in the United States. The complex interplay of physiological processes in persistent pain and dysfunctional sleep has been established. Recently, dysfunctional sleep has been identified as a potential pathway to the onset of painful TM disorder. Objectives: The aims were to (1) identify self‐report outcome measures (SROMs) of sleep quality that are clinimetrically sound in patients with painful TM disorders and (2) determine whether sleep dysfunction has any diagnostic or prognostic value for this population. Methods: A systematic search following PRISMA guidelines was run in six databases: CINAHL, Dental, PsychALL, PubMed, Scopus and Web of Science. Any study involving minors was excluded. Risks of biases were examined in all studies. Diagnostic pooled findings were reported. Results: Of the identified articles (n = 681), 18 were included in this systematic review (n = 1 clinimetric studies, n = 11 diagnostic studies, n = 6 prognostic studies). Nine different assessment tools were used; only the Pittsburg Sleep Quality Index (PSQI) has been validated in patients with painful TM disorders. Overall, sleep dysfunction was diagnostic for painful TM disorders. The pooled relative risk of sleep dysfunction was 1.71 (95% CI 1.30. 2.26). When PSQI scores were greater than 5/21, the unadjusted hazard ratio for development of painful TM disorders was reported to be 2.1. Conclusion: At present, the only SROM that has diagnostic and prognostic value in evaluating and managing patients with painful TM disorders is the PSQI.